Impact of Ionizing Radiation on Electrophysiological Behavior of Human-induced Ipsc-derived Cardiomyocytes on Multielectrode Arrays. Issue 1 (July 2018) - Becker, Benjamin V.; Seeger, Thomas; Beiert, Thomas; Antwerpen, Markus; Palnek, Andreas; Port, Matthias; Ullmann, Reinhard
Abstract : Abstract: Cardiac arrhythmia presumably induced through cardiac fibrosis is a recurrent long-term consequence of exposure to ionizing radiation. However, there is also evidence that cardiac arrhythmia can occur in patients shortly after irradiation. In this study, the authors employed multielectrode arrays to investigate the short-term effects of x-ray radiation on the electrophysiological behavior of cardiomyocytes derived from human-induced pluripotent stem cells. These cardiomyocytes with spontaneous pacemaker activity were cultured on single-well multielectrode arrays. After exposure to 0, 0.5, 1, 2, 5, 10 Gy x-ray radiation, electrical activity was measured at time points ranging from 10 min to 96 h. RNA sequencing was employed to verify the expression of genes specifically involved in cardiomyocyte differentiation and function. A decrease in beating rate was observed after irradiation with 5 and 10 Gy starting 48 h after exposure. Cells exposed to higher doses of radiation were more prone to show changes in electrophysiological spatial distribution. No radiation-induced effects with respect to the corrected QT interval were detectable. Gene expression analysis showed up regulation of typical cardiac features like ACTC1 or HCN4 . In this study, early dose-dependent changes in electrophysiological behavior were determined after x-ray irradiation. Results point towards a dose-dependent effect on pacemaker function of cardiomyocytes and indicate a possible connection between irradiation and short-term changes in electrophysiological cardiac function. Cardiomyocytes derived from human-induced pluripotent stem cells on multielectrode arrays represent a promising in vitro cardiac-modeling system for preclinical studies.